ANALISIS SISTEM INFORMASI AKUNTANSI PEMBAYARAN PAJAK KENDARAAN BERMOTOR PADA BADAN PENDAPATAN DAERAH PROVINSI SULAWESI UTARA UPTD PPD SAMSAT MANADO - Peggy Rumenser; Griffen Tigauw (Jurnal Akuntansi, 2025)
This study aims to analyze the accounting information system at the Regional Revenue Agency of North Sulawesi Province, UPTD PPD Samsat Manado, to evaluate its conformity with good accounting information principles. This descriptive qualitative research uses in-depth interviews, observation, and documentation to obtain valid and comprehensive data. The research findings indicate several systemic obstacles. In the online payment system, the identified issues include network disruptions, limited features, and suboptimal data integration. Meanwhile, the offline payment system faces potential delays in recording, long queues, and a risk of fraud or manipulation in direct transactions. Furthermore, the data backup system for the Samsat database is not yet optimal, which risks hindering services during technical disruptions. These obstacles hinder the achievement of transparency, accuracy, and effectiveness in motor vehicle tax collection. Despite these issues, the accounting information system implemented by the Regional Revenue Agency generally operates in accordance with accounting principles and regional financial administration procedures. The system encompasses the processes of recording, processing, and reporting local tax revenue, supported by applications such as SIMDA or SIPD. Therefore, a comprehensive evaluation of the accounting information system is crucial for improving service quality and taxpayer compliance.